Visual Memory 2022
DOI: 10.4324/9781003158134-14
|View full text |Cite
|
Sign up to set email alerts
|

Visual category-driven differences in memory

Abstract: Categorizing classes of stimuli in the real-world is thought to underlie features of general intelligence, including our ability to infer identities of new objects, environments, and people never encountered before. Our understanding of human categorization, and the neural mechanisms that underlie this ability, was initially described in the context of visual perception. It is now broadly accepted that a network of high-level visual areas on the ventral and lateral surfaces of the brain exhibit some level of '… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The findings reported by Srokova et al (2022) lead to a somewhat similar conclusion to that of Deng et al (2021). The study, which took the form of further analysis of the data reported by Hill et al (2021; see also Srokova et al, 2020), was motivated by prior evidence of systematic differences in the localization of encoding-and retrieval-related content-selective cortical activity, a phenomenon which had previously been examined in healthy younger adults only (Bainbridge et al, 2021;Steel et al, 2022). Specifically, mental imagery and retrieval of visual stimuli (such as scenes) has been reported to be associated with neural activity that peaks slightly anterior to the peak of the activity elicited during direct perception of the same items.…”
Section: Effects Of Age On Neural Reinstatementmentioning
confidence: 61%
“…The findings reported by Srokova et al (2022) lead to a somewhat similar conclusion to that of Deng et al (2021). The study, which took the form of further analysis of the data reported by Hill et al (2021; see also Srokova et al, 2020), was motivated by prior evidence of systematic differences in the localization of encoding-and retrieval-related content-selective cortical activity, a phenomenon which had previously been examined in healthy younger adults only (Bainbridge et al, 2021;Steel et al, 2022). Specifically, mental imagery and retrieval of visual stimuli (such as scenes) has been reported to be associated with neural activity that peaks slightly anterior to the peak of the activity elicited during direct perception of the same items.…”
Section: Effects Of Age On Neural Reinstatementmentioning
confidence: 61%
“…The findings reported by Srokova et al (2022) lead to a somewhat similar conclusion to that of Deng et al (2021). The study, which took the form of further analysis of the data reported by Hill et al (2021; see also Srokova et al, 2020), was motivated by prior evidence of systematic differences in the localization of encoding-and retrieval-related content-selective cortical activity, a phenomenon which had previously been examined in healthy younger adults only (Bainbridge et al, 2021;Steel et al, 2022). Specifically, mental imagery and retrieval of visual stimuli (such as scenes) has been reported to be associated with neural activity that peaks slightly anterior to the peak of the activity elicited during direct perception of the same items.…”
Section: Effects Of Age On Neural Reinstatementmentioning
confidence: 61%
“…Specifically, mental imagery and retrieval of visual stimuli (such as scenes) has been reported to be associated with neural activity that peaks slightly anterior to the peak of the activity elicited during direct perception of the same items. This retrieval-related bias toward more anterior neural recruitment has been termed the 'anterior shift' (Bainbridge et al, 2021;Rugg and Thompson-Schill, 2013; see also Steel 2022). Because the posterior-anterior axis of occipitotemporal cortex forms a gradient of increasing abstraction (Kravitz et al, 2013), the anterior shift might reflect a weighting in favor of representations that emphasize conceptual attributes of a stimulus event at the expense of its perceptual and sensory features.…”
Section: Effects Of Age On Neural Reinstatementmentioning
confidence: 99%
“…Additional studies have also found that a separate region, the amygdala, may play a role in face memory (e.g., Kleinhans et al, 2007). Therefore, it seems that there may not only be category-selective perceptual areas, but also category-selective memory areas, and that the perceptual areas may even drive the emergence of the memory ones (Steel & Silson, 2022). In fact, evidence suggests there may even be memory regions in the brain that contain information specific to a single image.…”
Section: Perception and Memory In The Brainmentioning
confidence: 99%